Benchmark of wrinkling formulae and methods for pre-sizing of aircraft lightweight sandwich structures. (1st October 2021) - Ginot, M.; D'Ottavio, M.; Polit, O.; Bouvet, C.; Castanié, B.
Abstract: Sandwich structures are widely used in many industrial applications and especially in light aviation. The local buckling phenomenon named "wrinkling" is one of the primary causes of compressive failure of such structures. Its calculation is a difficult practical problem since this phenomenon cannot be captured by the GFEM (Global Finite Element Model) classically used for aircraft structure sizing. Therefore, pre-sizing involves the use of a wrinkling model, which can be found in the literature. In practice, such models are used with high safety factors by the industry. This paper proposes an evaluation of analytical wrinkling formulas in an industrial setting. Realistic applications involve a framework (3D stress state, orthotropy, skin asymmetry) far from the assumptions on which most of the analytical formulations are based. The case study is a sandwich composite beam subjected to uni-axial compressive load. Limitations and assumptions of the analytical wrinkling models studied are quantified and a discussion on the relevance of using simple formulas for the design of sandwich structured composites is developed.